POST-MERGER BUSINESS SUSTAINABILITY STRATEGY AT PT SANDANG JAYA ABADI IN FACING COMPETITION IN THE GARMENT INDUSTRY IN BANDUNG - Anes Salim; Ridlwan Muttaqin; Ezra Karamang (CV. Radja Publika, 2025)
This study aims to analyze the business sustainability strategy of PT Sandang Jaya Abadi after the merger with SGJB Group in facing competition in the baby garment industry in Bandung. This study uses a qualitative descriptive method through interviews, observations, and company document studies. The analysis was conducted using the PESTEL and Porter's Five Forces models to assess the external conditions of the industry, as well as the IFE and EFE matrices to identify the company's internal and external factors. Furthermore, SWOT and TOWS were used to formulate alternative business sustainability strategies, and the Business Model Canvas was used to describe the company's post-merger business model. The results show that the company has strengths in production flexibility and stable product quality, but weak digital integration, high COGS, and post-merger operational coordination are the main obstacles. Opportunities come from increasing demand in e-commerce and local product trends, while threats arise from cheap imported products and price competition. Recommended strategies include production cost efficiency, operational system digitization, strengthening quality control, and optimizing digital-based marketing. This study is expected to serve as a reference for management in determining the direction of future business development strategies.